Tsunami Evacuation Drill System Focusing on Mobile Devices - Mitsuhara, Hiroyuki; Shishibori, Masami (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Natural disasters, such as tsunami, claim lives of many coastal residents every year. Therefore, tsunami evacuation drills are important for costal residents to survive tsunami. We developed a tsunami evacuation drill system that enables participants to evacuate and move to a shelter while occasionally glancing at a map-based tsunami simulation on mobile devices.The system has the following advantages: (1) a practitioner can easily customise the simulation, (2) the simulation can be displayed on a web browser and (3) the participants’ evacuation routes can be recorded and displayed on the simulation system.We conducted a preliminary comparative experiment with 18 university students and found that the developed system was accepted more by participants using a tablet rather than by those using smartglasses.